Synchronous occurrence of ileal stromal tumor (GIST) and colonic adenocarcinoma: a case report. - Trajkovska, Elizabeta; Janevska, Vesna; Spasevska, Liljana; Janevski, Vlado; Zhivadinovikj, Julija; Petrushevska, Gordana; Dukova, Blagica (My University, 2015)
Introduction: Gastrointestinal stromal tumors (GIST) are the most common mesenchymal tumors of the digestive tract. There is an increasing number of literature reports on synchronous occurrence of gastrointestinal stromal tumors and another malignancy of distinct etiology and evolution. The most reported cases include gastric synchronous occurrence of gastrointestinal stromal tumors and adenocarcinoma and gastric gastrointestinal stromal tumors and colonic adenocarcinoma. Case report: We present a case of a 77-old female, with synchronous cecal moderately differentiated adenocarcinoma in Stage IIA according to the TNM classification and ileal spindle cell type GIST with low malignant potential, positive for c-Kit, CD34, vimentin, Actin, and negative for S100. Conclusion: The synchronous occurrence of small bowel gastrointestinal stromal tumors and other primary gastrointestinal malignancies has been rarely reported. There is a need of further investigations to identify the relationship between gastrointestinal stromal tumors and colorectal cancers.